Water Conservation in the Qur’anic Perspective: A Thematic Analysis of Ethical Water Usage in Purification Rituals - Asrori, Mohammad; Muhammad, Muhammad; Nurul Yaqin, Mohamad Zubad; Firyal, Wafda; Wahidah, Finadatul (Studia Ecologiae et Bioethicae, 2025)
Water conservation represents a pressing global issue, especially in light of the growing scarcity of clean water resources. As the world’s second-largest religion, Islam places significant emphasis on the prudent and responsible use of water, both in religious rituals and in everyday life. This study investigates the concept of water conservation from a Qur’anic perspective, with particular attention to the ethical dimensions of water usage in purification practices. Employing critical thinking and analytical methodologies, it adopts a thematic exegesis approach within the interpretive framework of al-Adabī al-Ijtimāʻī. The findings indicate that the Qur’an presents water as a fundamental source of life, a symbol of purity, and a divine blessing that must be protected. Although Islam prescribes ritual purification before certain acts of worship, current practices of water use in these contexts frequently deviate from the conservation principles espoused in Islamic teachings. Therefore, fostering a collective ethical awareness among Muslims regarding water use is essential for minimizing waste and advancing sustainable conservation efforts.